RSPO3 antagonism inhibits growth and tumorigenicity in colorectal tumors harboring common Wnt pathway mutations. Issue 1 (December 2017) - Fischer, Marcus; Yeung, V.; Cattaruzza, Fiore; Hussein, Rajaa; Yen, Wan-Ching; Murriel, Christopher; Evans, James; O'Young, Gilbert; Brunner, Alayne; Wang, Min; Cain, Jennifer; Cancilla, Belinda; et al.
Abstract Activating mutations in the Wnt pathway are a characteristic feature of colorectal cancer (CRC). The R-spondin (RSPO) family is a group of secreted proteins that enhance Wnt signaling and RSPO2 and RSPO3 gene fusions have been reported in CRC. We have previously shown that Wnt pathway blockers exhibit potent combinatorial activity with taxanes to inhibit tumor growth. Here we show that RSPO3 antagonism synergizes with paclitaxel based chemotherapies in patient-derived xenograft models (PDX) with RSPO3 fusions and in tumors with common CRC mutations such as APC, β-catenin, or RNF43. In these latter types of tumors that represent over 90% of CRC, RSPO3 is produced by stromal cells in the tumor microenvironment and the activating mutations appear to sensitize the tumors to Wnt-Rspo synergy. The combination of RSPO3 inhibition and taxane treatment provides an approach to effectively target oncogenic WNT signaling in a significant number of patients with colorectal and other intestinal cancers.